A new cause of haemolytic anaemia in the newborn. A description of an unstable fetal haemoglobin: F Poole, alpha2-G-gamma2 130 trptophan yeilds glycine. Issue 4 (April 1975) - Lee-Potter, J P; Deacon-Smith, R A; Simpkiss, M J; Kamuzora, H; Lehmann, H
Abstract : In a newborn twin with haemolytic anaemia an unstable fetal haemoglobin was found to be the cause. The anaemia improved spontaneously with the disappearance of the fetal haemoglobin. The new Hb F (alpha2gamma2) variant was shown to have a glycine at position 130 of the 146 residues of the gamma chain. This portion is inside the globin molecule and in all known normal globins it is occupied by a residue with a bulky hydrophobic side chain. Its replacement by glycine which has no side chain would be expected to cause instability. The human gamma-chains may either have a glycine or an alanine at position 136. Evidence is brought forward to suggest that in the abnormal chain position 136 is occupied by glycine.